2017
DOI: 10.1038/nature23897
|View full text |Cite|
|
Sign up to set email alerts
|

The Apostasia genome and the evolution of orchids

Abstract: Constituting approximately 10% of flowering plant species, orchids (Orchidaceae) display unique flower morphologies, possess an extraordinary diversity in lifestyle, and have successfully colonized almost every habitat on Earth 1-3 . Here we report the draft genome sequence of Apostasia shenzhenica 4 , a representative of one of two genera that form a sister lineage to the rest of the Orchidaceae, providing a reference for inferring the genome content and structure of the most recent common ancestor of all ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
347
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 315 publications
(375 citation statements)
references
References 97 publications
(143 reference statements)
15
347
2
Order By: Relevance
“…Zhang et al (2017) indicated the possibility of an ancient orchid-specific whole-genome duplication (WGD) event shared by all extant orchids, which might be correlated with orchid diversification. Interestingly, it has been reported that DL/CRC represents a single orthologous lineage, without ancient duplications (Lee et al , 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (2017) indicated the possibility of an ancient orchid-specific whole-genome duplication (WGD) event shared by all extant orchids, which might be correlated with orchid diversification. Interestingly, it has been reported that DL/CRC represents a single orthologous lineage, without ancient duplications (Lee et al , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The conserved YAB domain based on the hidden Markov model (HMM) (PF04690) was obtained from the Pfam protein family database (http://pfam.sanger.ac.uk). To identify the YABBY transcription factor coding genes of orchids, the HMM profile of the YABBY domain was used as a query for an HMMER search (http://hmmer.janelia.org/) of the P. equestris , Dendrobium catenatum , and Apostasia shenzenica genome sequences (E-value=0.00001) (Cai et al , 2015; Zhang et al , 2016; Zhang et al , 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Although Antirrhinum did not experience a whole genome triplication, the duplicated region containing TCP genes on chromosomes 6 and 8 are closely associated with zygomorphic flower type, showing its unique evolutionary manner because no similar mechanism had been found in closely related species. For examples, one separated whole genome duplication led to partial zygomorphic type species of Glycine; and a MADS box family gene change resulting in symmetrical flowers in Orchidaceae 26,27 . In general, the ancient species are mostly radial symmetry and the newly derived species with symmetrical flowers.…”
Section: Discussionmentioning
confidence: 99%
“…The, Linked-reads technology (10x Genomics), has emerged as an alternative approach to obtain long-range sequence information and even construct haplotype specific assemblies while leveraging the high throughput, low cost, and accuracy of short-read sequencing. Recent de novo genome assembly projects have opted to combine different technologies [43][44][45] highlighting the benefit of hybrid genome assembly. Particularly important is the combination of highly accurate short-read SGS technologies with long-read TGS technologies.…”
Section: Discussionmentioning
confidence: 99%